MECHANICAL, BARRIER AND ANTIOXIDANT PROPERTIES OF EDIBLE FILMS MADE FROM WHEY PROTEIN ISOLATE INCORPORATED WITH GREEN TEA EXTRACT - & Abdul-Rahman, Chalob (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The aim of this research was to study the effect of adding green tea extract (GTE) on the mechanical, oxygen permeability, water vapor permeability and antioxidant properties of whey protein isolate edible films. Edible films incorporated with the alcoholic extract of green tea showed high antioxidant activity as compared with the standard antioxidant BHA (Butylated hydroxyl anisole), The scavenging values of the film with GTE and the control film were 65.22% and 9.5%, respectively. The mechanical tests, revealed a decreasing in thickness in the control film which was formed without GTE from 181 μm to 169 μm. The tensile strength has been reduced in the film to 7.87 MPa where it was in the control sample 8.29 MPa. However, the elongation rate increased to 117% in the film supported by the extract, which was higher than the elongation rate of the control protein film without GTE (107%). The permeability value of oxygen (OP) and water vapor permeability (WPV) were measured and the properties of film were evaluated. The OP value of the control film was 90.07 ml / m 2 * day, whereas the permeability of the film with (GTE) decreased to 72.45 ml / m 2 * day. The WVP value of the control film was 0.61(gm.mm / hr. m2. mPa), while the permeability value of the film with GTE was 0.22 (gm.mm / hr. m2. MPa). The water solubility of film with GTE was increased to 47.5% as compared to the control film which was 41.2%.In respect to the optical properieties the ∆E value of supported film samples was 29.09%,and  (L, a, b) (28.3,-7.41, 51.01) respectively, while for  the control Sample ∆E  was 9.6% (L, a, b), (6.6,-9.27, 59.15) respectively.